Enterprise 2.0 how social software will change the future of work - Cook, Niall (Hants Ashgate Pub., 2008)
Social software has taken the Internet by storm, fuelling huge growth in collaborative authoring platforms (such as blogs, wikis and podcasts) and massive expansion in social networking communities. These technologies have generated an unprecedented level of consumer participation and it is now time for businesses to embrace them as part of their own information and knowledge management strategies. Enterprise 2.0 is one of the first books to explain the impact that social software will have inside the corporate firewall, and ultimately how staff will work together in the future. Niall Cook helps you to navigate this emerging landscape and introduces the key concepts that make up 'Enterprise 2.0'. The 4Cs model at the heart of the book uses practical examples from well known companies in a range of industry sectors to illustrate how to apply Enterprise 2.0 to encourage communication, cooperation, collaboration and connection between employees and customers in your own company. Erudite, well-researched and highly readable, this book is essential for anyone involved in knowledge, information and library management, as well as those implementing social software tools inside organizations. It will also appeal to marketing, advertising, public relations and internal communications professionals who need to exploit the opportunities social software offers for significant business impact and competitive advantage.
Includes bibliographical references (p. 153-159) and index.
Keywords: Management--Communication systems--Social aspects